Clinical Efficacy of Oligofructans from Ophiopogon japonicus in Reducing Atopic Dermatitis Flare-ups in Caucasian Patients - Carine Mainzer; Maud Le Guillou; Raoul Vyumvuhore; Bernard Chadoutaud; Sylvie Bordes; Brigitte Closs (Medical Journals Sweden, 2019)
Atopic dermatitis is a chronic relapsing inflammatory skin disease affecting 15-20% children and 2-10% adults worldwide. Topical treatments include corticosteroids and calcineurin inhibitors, despite frequently observed adverse events such as skin atrophy, itching and burning sensations. Good alternatives that can prolong disease relief in between flare-ups are therefore needed. We conducted a randomized, single-blind, placebo-controlled, multicenter clinical trial in a Caucasian cohort of 90 children and 144 adults with mild-to-moderate atopic dermatitis that applied tested products twice daily for 60 days. A natural active from Ophiopogon japonicus, that improves atopic dermatitis symptoms in vivo, was successful in reducing the SCORing of Atopic Dermatitis (SCORAD), including erythema, pruritus and body surface area in both cohorts. The active also improved patient's quality of life and significantly reduced the number of patients relapsing compared to placebo. We conclude that this treatment could be an effective solution to help control the disease in between flare-ups.